2022
DOI: 10.3389/fpubh.2022.873891
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Anxiety in Spain: A Gendered Approach One Year After the Start of COVID-19 Pandemic

Abstract: The COVID-19 pandemic has an impact on mental health. However, there is little evidence on how different axes of social inequity influence mental health from a gender perspective and over time. Our aim is to analyze anxiety according to gender identity and other axes of social inequities (migration status, sexual orientation, age, and employment conditions) one year after the start of the COVID-19 pandemic in Spain. We conducted a cross-sectional study among adults living in Spain with an online survey from Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…A notable new finding of the current study is that although the number of students who reported higher anxiety and lower mood compared to pre-confinement had decreased slightly one year post-confinement, this number still clearly exceeded the number of students who reported the opposite. As reported in other studies of the Spanish population [ 70 , 71 ], women were more affected by anxiety than men during COVID-19 pandemic. Students with obesity were the only group with a higher proportion of participants with more anxiety and lower mood status one year post-confinement than during the confinement period.…”
Section: Discussionsupporting
confidence: 72%
“…A notable new finding of the current study is that although the number of students who reported higher anxiety and lower mood compared to pre-confinement had decreased slightly one year post-confinement, this number still clearly exceeded the number of students who reported the opposite. As reported in other studies of the Spanish population [ 70 , 71 ], women were more affected by anxiety than men during COVID-19 pandemic. Students with obesity were the only group with a higher proportion of participants with more anxiety and lower mood status one year post-confinement than during the confinement period.…”
Section: Discussionsupporting
confidence: 72%
“…Another important discussion is around the profound impact of the crisis of care on women. Previous research has already indicated the lack of attention to women’s unpaid labour and the costs of fulfilling care roles (Folbre, 2006a ), as well as women’s increased vulnerability in the context of health crises, especially among the racialized or migrant populations (Azcona et al, 2020 ; Cohen & van der Meulen Rodgers, 2021 ; Doyal, 1996 ; Jacques-Aviñó et al, Harman, 2016 ; Jacques-Aviñó et al, 2020 , 2022 ; Sherman, 2020 ; Smith et al, 2021 ; Wenham et al, 2020 ). However, a generalized lack of gendered political and economic responses to the COVID-19 syndemic prevails (Smith et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In both scenarios, the importance of self-care during periods of lockdown and, overall, throughout the COVID-19 syndemic needs to be discussed. An increasing amount of evidence on the impact of COVID-19 on mental and emotional health has been published (Jacques-Aviñó et al, 2022 ; Gloster et al, 2020 ). Academics worldwide have made a call to prioritize mental health science and public health actions directed to protecting and promoting mental health and its determinants (Holmes et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we aimed at analyzing if COVID-19 vaccine trials accounted for axes of social inequities in the description of participant characteristics, follow-up, and results about efficacy and safety. In particular, we focused on those social and demographic factors which alters the access to health care and are involved in health inequities: age, sex, gender identity, sexual orientation, socioeconomic status, race, ethnicity, and obesity ( 10 , 12 ). We included obesity because its social stigma promotes health barriers ( 13 ), and makes communication difficult.…”
Section: Introductionmentioning
confidence: 99%